ASPEK-ASPEK INDIVIDUAL TERHADAP PERTIMBANGAN PROFESIONAL AUDITOR - Wiwi Idawati (Behavioral Accounting Journal, 2021)
The goal of this research was to determine “the effect of work experience and gender on audit judgement either partially or simultaneously”. This research is using “a causal-comparative and collection of data by distributing questionnaires to 101 auditors in 30 public accounting firm in Jakarta registered in 2013, with a minimum level position as a senior auditor to partner”. Tests conducted are “validity and realibility, classical assumption and hypothesis testing with multiple linear regression method”. This research was processed through the IBM SPSS 22 with research results showing that “simultaneously work experience and gender significantly affect audit judgement while partial, work experience is significant influence but gender is not significantly affect audit judgement”. For the Accountant Public Office should be open to the research, respondents should be more serious for reading the questions in the questionnaire and come to more training and seminars. For further research, we recommend adding another independent variable and the measurement of gender, should get the number of respondents men and women in equal numbers, so that the results obtained is presented facts on the ground.